2005
DOI: 10.1080/13625180500131360
|View full text |Cite
|
Sign up to set email alerts
|

Client participation and provider communication in family planning counselling and the sample study from Turkey

Abstract: The single strongest factor was providers giving biomedical and technical information. The qualitative analysis of audiotapes found that most of clients' questions concern contraceptive side effects and symptoms. The next category social talk, consisted largely of greetings. Most of the providers (87.6 %) are women. The results show that providers dominate most counselling session and clients rarely take on active role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Our finding of a lack of provider involvement in or facilitation of decision making in the majority of family planning visits is similar to findings in the developing world [15][16][17][18] and is consistent with research on the philosophy of counseling in family planning programs, which emphasizes an autonomous model of decision making because of the personal nature of the reproductive health context. 19,28,35 While we were not able to determine the intentions of the providers in our sample, both the informed choice and the foreclosed models may be motivated by a desire to prioritize patient autonomy in the decision-making process.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding of a lack of provider involvement in or facilitation of decision making in the majority of family planning visits is similar to findings in the developing world [15][16][17][18] and is consistent with research on the philosophy of counseling in family planning programs, which emphasizes an autonomous model of decision making because of the personal nature of the reproductive health context. 19,28,35 While we were not able to determine the intentions of the providers in our sample, both the informed choice and the foreclosed models may be motivated by a desire to prioritize patient autonomy in the decision-making process.…”
Section: Discussionsupporting
confidence: 89%
“…14 Research that has directly documented the contraceptive counseling dynamic has been largely limited to studies in the developing world, and these studies have found that family planning counseling sessions are often dominated by the provider. [15][16][17][18] Even when the patient is the one ultimately making the decision about which method to use, there is often minimal provider engagement with patients to determine their preferences and concerns about methods and how these issues relate to available options. 19,20 Given the increasing recognition of the value of patient-centered care, in which there is a focus on patients' preferences and experiences, 21 interventions to enhance patient-provider engagement during contraceptive decision making could improve the counseling experience, which may positively influence contraceptive use.…”
mentioning
confidence: 99%
“…Qualitative studies of U.S. women's counseling experiences have found that women often report being dissatisfied with the counseling they receive, and that many are concerned that providers do not fully disclose the potential side effects of methods . Research that has directly documented the contraceptive counseling dynamic has been largely limited to studies in the developing world, and these studies have found that family planning counseling sessions are often dominated by the provider . Even when the patient is the one ultimately making the decision about which method to use, there is often minimal provider engagement with patients to determine their preferences and concerns about methods and how these issues relate to available options …”
Section: Introductionmentioning
confidence: 99%
“…14 Research that has directly documented the contraceptive counseling dynamic has been largely limited to studies in the developing world, and these studies have found that family planning counseling sessions are often dominated by the provider. 1518 Even when the patient is the one ultimately making the decision about which method to use, there is often minimal provider engagement with patients to determine their preferences and concerns about methods and how these issues relate to available options. 19,20 …”
mentioning
confidence: 99%
“…However, Mohammad Alizadeh et al (2008) have indicated employees' shyness in discussing family planning issues, particularly when speaking with men (9). Mohammad Alizadeh et al (2009) and Kirimlioglu et al (2005) in their studies about the family planning services have reported the silence and inactiveness of the clients in talking about their needs as a barrier in the consultation process (6, 14). In this study, most of managers and employees were agreeing on the clients’ lack of interest in participating in the process of family planning consultation.…”
Section: Discussionmentioning
confidence: 99%